Dystrophic Muscle Affects Motoneuron Axon Outgrowth and NMJ Assembly. Issue 7 (17th March 2022) - Fornetti, Ersilia; Testa, Stefano; De Paolis, Francesca; Fuoco, Claudia; Bernardini, Sergio; Pozo Devoto, Victorio; Stokin, Gorazd Bernard; Giannitelli, Sara Maria; Rainer, Alberto; Bigot, Anne; Zoccali, Carmine; Baldi, Jacopo; et al.
Abstract: The Neuromuscular Junction (NMJ) is a chemical synapse localized between the terminal branches of the spinal motor neurons and myofibers. In the past two decades coculture systems to generate the NMJ in culture are developed to address concerns about animal models, despite the complexity of its highly specialized structure makes the in vitro modeling a challenging task. Microfluidics, unlike mass cocultures, allow spatial and temporal control over different microenvironment by manipulating either neural cells or muscle cell populations independently. Therefore, exploiting an organ‐on‐a‐chip approach, the aim is to obtain a reliable and predictive in vitro human model of NMJ in physiological and pathological conditions, to investigate the occurrence of synapse detriment in α‐sarcoglycanopathy, a subtype of limb‐girdle muscular dystrophy. For this purpose, motor neurons derived from human induced pluripotent stem cells (hiPSCs) and either healthy or α‐sarcoglycan mutant human myogenic progenitors are seeded in two separated chambers of a microfluidic device. Differentiated myotubes and hiPSCs‐derived motor neurons on‐chip are able to establish points of interaction where pre‐ and postsynaptic structures colocalize. Moreover, the attraction of motor neurons axons by muscle fibers and the NMJ maturation appear to be affected by the muscular compartment, being impaired by the dystrophic cellular component. Abstract : The human Neuromuscular Junction is recreated in vitro by exploiting the microfluidic technology that allows to maintain separate but communicating motor neurons and muscle cells in a physiologically relevant way. This approach highlights defects in the neural elongation of healthy motor neurons cocultured with α‐sarcoglycan mutant muscle cells and less clustered AChRs on the diseased myotubes.